Hearing loss in a child with hydrocephalus - -, Muyassaroh; Marliyawati, Dwi; Affendi, Ahmad (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Hydrocephalus can cause hearing loss through the mechanism of the relationship between pressure cerebrospinal fluid (CSF), perilymph, and endolymph. Hidrocephalus is rare, estimated at 10 per mil. Most cases in infants (46.25%), neonates (5%). Men are more likely to experience hydrocephalus. Changes in pressure and loss of CSF cause endolymph hydrops which results in inner ear dysfunction Objective : To study how cases of hydrocephalus cause hearing loss. Case:Reported a case of a woman aged 1 year 7 months with hearing loss and hydrocephalus Methods: Search literature through Pubmed, Google Scholar. with the keywords hearing loss AND hydrocephalus AND children obtained 101 journals. The results of the screening obtained 4 analyzed journals. Result : Hearing loss was caused by IV ventricular pressure. Improvement of CSF pressure with VP shunt or ventriculotomy can improve inner ear function Conclusion: Hydrocephalus causes endolymph hydrops which results in hearing loss.